(3HTQi GdcFjH HdbGA GdMHjHs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hSdGe Ydi YHGOg GdPjfEUWai gPG LRA SejJg HTQi GdcFjH HdbGA GdMHjH dNUJg e cJGH GdcHjQ GdPi CdaJg ai CMhGd GdHQRN bUQJg Ydi GdHTQi s
(3BNQgG (B:s
(3Yf CHj gQjQI QVi Gddg Yfg bGd bGd QShd Gddg Udi Gddg Ydjg hSde ChdGO GdeDefjf ai LHd ai GdLfI jcadge EHQGgje hSGQg MJi jQOge Edi BHGFge jhe GdbjGeI Je GdcJGH hddg GdMeO hGdefI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B18s
(3HgG eWGdH ddcJGHs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds